Mortalidade por asma no estado de Sergipe, uma tendência secular de 35 anos - Fernandes, Manuella de Oliveira Mota (2019)
Introduction: Asthma is a disease that can be reversible through treatment or spontaneously, but has been poorly controlled due to inadequate prescription as well as misuse of medications. Brazil occupies the third place in the ranking of hospitalizations for clinical diseases and the fourth in deaths due to respiratory diseases. Regarding mortality, there are no reliable national data on asthma mortality trends in Brazil, since death records are incomplete and are not performed by all States. Objective: To provide data on the mortality trend in the State of Sergipe in the years 1980 to 2015. Methods: Data were obtained through the collection of data from the Mortality Information System of the State of Sergipe. The analysis of the age-specific rates was performed by grouping the data in the following age groups: 0 to 19, 20 to 44, 45 to 64 and 65 years of age onwards. To analyze the mortality trends, we used the Joinpoint Regression Program version 4.5.0.1, based on the calculation of the annual percentage change (APC) and its respective 95% confidence intervals (95% CI), as well as SPSS statistic version 22. Results: A total of 1,292 deaths from asthma were recorded, peaking in 2007 among females, while males were in 2011. The highest mortality coefficient was found at ages over 65 years in both genders, representing 51% of the total. Another age group that presented a growing mortality trend was the group of 45 - 64 years old in both sexes. When analyzing the health regions, in the Aracaju region it was possible to verify a high mortality rate, but it was the only region that showed no tendency to mortality, unlike the Lagarto Region. Conclusion: infant and juvenile mortality presented a significant reduction, on the other hand, senile mortality obtained a constant growth in both sexes. Regarding the health regions, the Aracaju health region showed a reduction in the trend in mortality.